Optimization of Chocolate Drink Production at MSMEs Grah Indonesia using The Simplex Method - Juanda Juanda; Sri Hartuti; Rita Khathir; Raida Agustina; Ahlillah Ahlillah (LPPM Universitas BSI, 2023)
Micro, small, and medium enterprises (MSMEs) play an important role in economic growth in various regions of Indonesia. MSME Grah Indonesia produces chocolate drinks with three products, namely grass jelly cappuccino, taro, and chocolate pop ice. The weaknesses of the MSME Grah Indonesia include limited management capabilities, capital, technology, market access, technical and non-technical costs in the field that are difficult to avoid. The study aimed to maximize the production profit of SMEs Grah Indonesia and determine the optimal number and types of beverage products using the simplex method. The simplex method can be used to maximize or minimize based on the constraint function or available resources. The results shows that the profit of the contemporary chocolate drink production of MSMEs Grah Indonesia is IDR 2,000,000 per month, with a total production of 200 cups of grass jelly cappuccino (Xâ‚), 67 cups of taro (Xâ‚‚), and 400 cups of chocolate pop ice (Xâ‚ƒ). The raw materials needed to produce contemporary chocolate drinks at MSME Grah Indonesia are 20 kg of sugar, 10 liters of sweetened condensed milk, 200 sachets of cappuccino powder, 2 kg of taro powder, 400 sachets of chocolate pop ice powder, and grass jelly 10 kg.Â